VARIASI KETEBALAN MEDIA FILTER ARANG AKTIF TONGKOL JAGUNG TERHADAP PENURUNAN KADAR BESI (Fe) AIR BERSIH DI PT. XYZ - Ahmad fauzan Fauzan; Sadono setyoko; Agus Somad Saputra (Politeknik Kesehatan Kemenkes Bandung, 2021)
Water is a basic need for human life on this earth . In accordance with its use Water is very important for industrial activities , the need for clean water in the industry is divided into two, namely water for production and sanitation hygiene , for that clean water must meet good requirements in physical , chemical , and biological . Quality Chemical water in PT.Xyz for levels of Fe does not meet the requirements with levels of Fe of 1 , 56 mg / l, for it needs to do the processing of water by means of filtration . Filtration using a medium charcoal activated cob of corn . The treatment in research is to use variations of the thickness of the filter medium charcoal activated cob of corn with the thickness of the filter medium 30 cm, 40 cm and 50 cm, with the purpose to know the difference variation filter media to decrease the levels of Fe. This type of research is an experimental research design with pretest and post test without control . Mechanical taking samples that do that grab sampling . Based on the results of research filtration with a filter media charcoal activated cob corn thickness of 30 cm was able to lower the levels of Fe 89.04% , the filter medium charcoal activated cob corn thickness of 40 cm was able to lower the levels of Fe 94.53 %, and the media filter charcoal activated cob corn thickness 50 cm was able to reduce Fe content of 96.50%. In the study of this industry can use the media filter Charcoal On Cobs Corn thickness of 50 cm . because it is based on research by media filters Charcoal On Cobs Corn thickness of 50 cm can lower the levels of Fe of 0.046 mg / l and percent tase a decrease of 96.50%.